Prozeduren als Diskurshandlungen im glottodidaktischen Prozess - Lewicka, Grażyna (Glottodidactica, 2007)
The glottodidactic system is a specific communication system, in which learners acquire a language by means of a language. From the anthropological point of view language is a human property and does not exist independently of the human mind. Only texts exist independently as products of human activity created by means of internalized formation and functional rules. Hence language can be neither taught nor transmitted to the learner. Language can only be acquired by the interaction with the environment. Therefore it is of great importance for the learning process to introduce appropriate didactic procedures which help the learners to develop communication skills in authentic-like situations by means of discursive activities.